Manganese(IV) Complexes Derived from Polyfunctional Dihydrazone: Structural, Electrochemical and Antimicrobial Studies - Sarma, P.; Mahanta, P.; Basumatary, D.; Medhi, C. (Asian Journal of Chemistry, 2021)
Manganese(IV) complexes viz. [MnIV(nagh)(A)2]·2H2O and [MnIV(nagh)(NN)] have been synthesized from ligand bis(2-hydroxy-1-naphthaldehyde)glutaryldihydrazone (naghH4) and auxiliary ligands, A = H2O (1)/pyridine (2)/2-picoline (3)/3-picoline (4)/4-picoline (5) or NN = 2,2′-bipyridine (6)/1,10-phenanthroline (7). The elemental analysis, mass spectral and thermal studies supported the composition of all the manganese(IV) complexes. Structural aspects were determined from magnetic susceptibility, molar conductivity and spectral studies i.e. electronic, electron spin resonance and infrared. Their non-electrolytic nature were determined from molar conductances. Results from studies of magnetic moment, electronic and ESR suggested Mn(IV) ion in six-coordinate octahedral stereochemistry. The ligand coordinated to the metal in enolic form as a tetradentate in an anti-cis configuration as was correlated from IR data. Redox activities and antimicrobial potential against few Gram-positive and Gram-negative bacteria have been investigated for the dihydrazone and some manganese(IV) complexes.